A Survey of University Policy Makers’ Preferences and Expectations for Provincial Examinations - Traub, Ross E.; McLean, Leslie D. (Canadian Journal of Higher Education, 1985)
A survey was conducted of persons responsible for making undergraduate admission policies at Ontario universities to ascertain their preferences and expectations for provincial examinations. Fifty-eight individuals, at least two from each university, responded to a series of questions by telephone interview or questionnaire. Strong support was expressed for the reintroduction of provincial examinations for mathematics and first language (English or français) courses in the final year of the secondary school program. Most respondents rejected the use of scores on province-wide examinations for rating secondary schools and adjusting school marks. Instead, they expressed a preference for having applicants report both teacher-assigned course marks and provincial examination scores.